Frame dependence of the pair contribution to the pion electromagnetic form factor in a light-front approach - Melo, J. P. B. C. de [UNESP]; Frederico, T.; Pace, E.; Salmè, G. (Sociedade Brasileira de Física, 2003)
The frame dependence of the pair-term contribution to the electromagnetic form factor of the pion is studied within the Light Front approach. A symmetric ansatz for the pion Bethe-Salpeter amplitude with a pseudo scalar coupling of the constituent to the pion field is used. In this model, the pair term vanishes for the Drell-Yan condition, while it is dominant for momentum transfer along the light-front direction.